Matrix Isolation Study of the Conformations and Photochemistry of S‑Ethyl Fluorothioformate, FC(O)SCH2CH3 - Rodriguez Pirani, Lucas Sebastian (2014)
The IR spectra of S-ethyl fluorothioformate, FC(O)SCH2CH3, were recorded in the vapor phase and compared with the Raman spectrum in the liquid state. Additional IR spectra of the compound isolated in argon and nitrogen matrices at ca. 12 K were also recorded. The title compound exhibits rich conformational equilibria at room temperature being C1 the most stable symmetry with a synperiplanar orientation of the carbonyl double bond (C O) with respect to the S−C(sp3 ) single bond, while the C−C bond of the ethyl group presents a gauche orientation with respect to the C−S single bond. Several bands assigned to a second conformer were also observed in the IR matrix spectra. This second rotamer presents a planar skeleton (Cs point group) retaining the prevalent syn orientation of the FC(O)SCH2CH3 molecule with an antiperiplanar orientation of the C−C bond of the ethyl group with respect to the C−S bond. The variation of the nozzle temperature before matrix gas deposition gives rise to different conformer ratios. With these data an enthalpy difference of 0.45 kcal mol−1 can be calculated between the more stable C1 and the Cs conformers. A third form, corresponding to the anti-gauche conformer, is also detected when the matrix is exposed to broad-band UV−visible irradiation. Moreover, the photochemistry of the Ar and N2 matrix-isolated species is studied. Conformational interconversion is observed at short irradiation times, whereas a decarbonylation process with the concomitant formation of a HC(S)CH3:HF molecular complex dominates the photochemistry of FC(O)SCH2CH3 of longer irradiation times. The new ethyl fluoro sulfide, FSCH2CH3, is proposed as an intermediate species.